Young Iranian women as agents of social change: A qualitative study. (March 2020) - Salehi, Asiyeh; Sebar, Bernadette; Whitehead, Dean; Hatam, Nahid; Coyne, Elisabeth; Harris, Neil
Abstract: Objectives: Limited studies have investigated detailed insights into the experiences of women in transitioning countries such as Iran as active agents in their lives and their societies. This study explores how young Iranian women build and use their social capital to make a social change and improve their status. Methods: This study is the qualitative component of a larger mixed-method study exploring social capital and wellbeing in young Iranian women. Semi-structured, in-depth interviews were conducted with 17 young Iranian women aged 18–35. This data was supplemented with the open-ended responses provided by 87 of 391 participants in the quantitative phase of the study. Thematic analysis based on the Giorgi method was used for data analysis. Results: Two major themes that emerged from the data included "multiple identities" and "young women as agents of social change", with more emphasis on the latter. Four main strategies were used by young Iranian women to enact social change and improve their position. These included building digital freedom, generating a new style of dressing, creating leisure opportunities, and changing social and sexual relationships . Conclusions: This study provides new insights into the necessity of moving away from simply looking at women as powerless victims within paternalistic societies to exploring their potential as agents of social change. Understanding the ways young Iranian women perceive themselves, their roles in society and their experience of enacting social change and building new social identities yields deeper insights into their expectations for transformational change. Highlights: Women are agents of social change, not powerless victims within paternalistic societies. Iranian women are at the forefront when it comes to breaking down the boundaries and taboos, changing collective social capital. Protests by Iranian women are reflected in greater equality in participation in society and more open interactions. Social media is a strategic tool used by women to share their concerns about discriminatory challenges in society. Iranian women believe in evolution (strong and consistent change), rather than revolution (temporary and unsustainable change).